2015
DOI: 10.1016/j.neuropharm.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-seeking is associated with PKC-dependent reduction of excitatory signaling in accumbens shell D2 dopamine receptor-expressing neurons

Abstract: Stimulation of D1-like dopamine receptors (D1DRs) or D2-like dopamine receptors (D2DRs) in the nucleus accumbens (NAc) shell reinstates cocaine seeking in rats, an animal model of relapse. D2DRs and D1DRs activate protein kinase C (PKC) and recent studies indicate that activation of PKC in the NAc plays an important role in the reinstatement of drug seeking induced by a systemic cocaine priming injection. In the present study, pharmacological inhibition of PKC in the NAc shell attenuated cocaine seeking induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 77 publications
5
25
1
Order By: Relevance
“…As our mouse model disrupts PKC-mediated phosphorylation of GluA2, the current results may seem to conflict with findings that PKC inhibitors block reinstatement behavior (Famous et al, 2008; Ortinski et al, 2015) and can reverse some forms of cocaine-induced plasticity (McCutcheon et al, 2011a). However, along with its actions on GluA2 subunits, PKC also phosphorylates GluA1 subunits at multiple different residues.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…As our mouse model disrupts PKC-mediated phosphorylation of GluA2, the current results may seem to conflict with findings that PKC inhibitors block reinstatement behavior (Famous et al, 2008; Ortinski et al, 2015) and can reverse some forms of cocaine-induced plasticity (McCutcheon et al, 2011a). However, along with its actions on GluA2 subunits, PKC also phosphorylates GluA1 subunits at multiple different residues.…”
Section: Discussioncontrasting
confidence: 90%
“…In contrast to the consequences of PKC-mediated phosphorylation of GluA2, PKC-mediated phosphorylation of GluA1 has been shown to lead to both increased synaptic delivery of AMPA receptors as well as increased conductance of these receptors (Boehm et al, 2006; Jenkins and Traynelis, 2012; Lee et al, 2003; Tao et al, 2014; Wang et al, 2013). Consistent with this, inhibition of PKC leads to a decrease in evoked EPSCs within the nucleus accumbens (Ortinski et al, 2015), demonstrating that disruption of all PKC activity has the opposite effect on both physiology and behavior compared to our findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings suggested that D2DR may govern dorsal horn neuronal adaptation during chronic morphine exposure. It should be noted that PKC can be activated by D2DR39. PKC is widely accepted as a downstream of NMDA receptor in morphine tolerance, however, the activated PKC is also reported can activate NMDA receptor to further promote the central sensitization40.…”
Section: Discussionmentioning
confidence: 98%
“…88,107 Cocaine reinstatement (a model of relapse) following withdrawal is at least partially due to D2R-dependent increases in PKC signaling in the NAc shell with increased D1R or direct pathway signaling to promote relapse. 108 Indeed, a study of cocaine-primed reinstatement of cocaine-seeking behavior showed an increase in phosphorylated PKCγ. 109 Injection of PKC inhibitors into the NAc core inhibits cocaine-seeking in rats while injection of inhibitors into the ventral tegmental area reduces dopamine release in the NAc as well as cocaine-induced hyperlocomotion.…”
Section: S-glutathionylation Of Pka Pkc Cdk5 and Actin May Inflmentioning
confidence: 99%